(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This article has studied the language of persuasion in advertising texts and has examined persuasion in some Persian newspapers with an emphasis on the gender variable. This study was conducted by analytical approach and its data was collected from Iran’s most important and widely circulated newspapers. The study results suggested that in persuasive texts of newspapers, the advertisers encourage viewers and audiences to buy the products by emphasizing on some characteristics specific to women such as beauty, adornment and housewifery as well as some special characteristics of men such as fitness, social prestige, responsibility and the role of being a provider. The findings indicated that the studied texts had characteristics in such a way that they use specific linguistic components and literary forms such as foregrounding, alliteration, hyperbole and exaggeration, metaphors and ambiguity to convey the desired concepts and attract the audience according to gender. Thus, the gender variable is an effective factor in the structure of persuasive texts related to advertising in Persian newspapers. The results of the research implied the fact that gender differences have been reflected in advertising in the form of language and other specific metalinguistic elements such as ideology and culture, and these linguistic and metalinguistic strategies are employed differently for men and women, in a way that this unequal gender approach seems to be man-centered.